2016
DOI: 10.3758/s13423-016-1023-8
|View full text |Cite
|
Sign up to set email alerts
|

Is cognitive control automatic? New insights from transcranial magnetic stimulation

Abstract: Cognitive control has been classically considered as a flexible process engaged to pursue intentional behaviors, as distinct from automatic processes, which are unintentional, inflexible, and triggered by unconscious mechanisms. Our study challenged this view, showing that such a distinction may not be so clear-cut. We analyzed motor-evoked potentials (MEPs) elicited by transcranial magnetic stimulation to investigate the neurocognitive mechanisms occurring in a conflict task during trials that either required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…Studies reported evidence for motor activity associated with sequential effects even if trials did not require a motor response (Cona, Treccani, & Umiltà, 2016). More specifically, these authors used TMS applied over M1 at 200 ms after stimulus presentation during a Go/No-go Simon task.…”
Section: Tms and Key Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies reported evidence for motor activity associated with sequential effects even if trials did not require a motor response (Cona, Treccani, & Umiltà, 2016). More specifically, these authors used TMS applied over M1 at 200 ms after stimulus presentation during a Go/No-go Simon task.…”
Section: Tms and Key Questionsmentioning
confidence: 99%
“…They found that MEP activity was modulated by sequential effects even if the participant knew in advance that the upcoming trial would be a no-go trial. In light of this evidence, Cona, Treccani and Umiltà (2016) concluded that cognitive control may be automatically implemented and cannot only operate without awareness of the conflict but also without an intention to select a response (Desender & Van den Bussche, 2012;van Gaal, Lamme, & Ridderinkhof, 2010). Also, these results could be explained because integration of the stimulus features does not require intention to select a response.…”
Section: Tms and Key Questionsmentioning
confidence: 99%
“…In a response conflict task, such as the flanker task, suppression of irrelevant and conflicting response information is typically more efficient on the trial after an individual has successfully resolved such conflict (Botvinick, Braver, Barch, Carter, & Cohen, 2001;Gratton, Coles, & Donchin, 1992). Such conflict adaptation effects are evident in motor-evoked potentials even when the prior and current trials required no behavioral response, and thus when no conflict in response selection required resolution, consistent with the idea that the response associations of the stimuli (which were arbitrary and defined by the task goals) were processed automatically in a cue-driven fashion (Cona, Treccani, & Umiltà, 2016).…”
Section: Flexibility Of Automatic Information Processingmentioning
confidence: 61%
“…Yet, participants also carried out a detection task in which arrow targets pointing left or right were used, to test another hypothesis. It has been shown that response conflict is detected by the brain, even when participants simply view the screen without responding 48 . Thus, it could be that participants also have an experience of subjective difficulty during the detection task based on the mismatch between prime and arrow target, even though they do not respond to the targets.…”
Section: Discussionmentioning
confidence: 99%